Post-arrest therapeutic hypothermia in pediatric patients with congenital heart disease. (May 2018) - Cheng, Henry H.; Rajagopal, Satish K.; Sansevere, Arnold J.; McDavitt, Erica; Wigmore, Daniel; Mecklosky, Jessica; Andren, Kristofer; Williams, Kathryn A.; Danehy, Amy; Soul, Janet S.
Abstract: Background: While therapeutic hypothermia (TH) is an effective neuroprotective therapy for neonatal hypoxic-ischemic encephalopathy, TH has not been demonstrated to improve outcome in other pediatric populations. Patients with acquired or congenital heart disease (CHD) are at high risk of both cardiac arrest and neurodevelopmental impairments, and therapies are needed to improve neurologic outcome. The primary goal of our study was to compare safety/efficacy outcomes in post-arrest CHD patients treated with TH versus controls not treated with TH. Methods: Patients with CHD treated during the first 18 months after initiation of a post-arrest TH protocol (temperature goal: 33.5 °C) were compared to historical and contemporary post-arrest controls not treated with TH. Post-arrest data, including temperature, safety measures (e.g. arrhythmia, bleeding), neurodiagnostic data (EEG, neuroimaging), and survival were compared. Results: Thirty arrest episodes treated with TH and 51 control arrest episodes were included. The groups did not differ in age, duration of arrest, post-arrest lactate, or use of ECMO-CPR. The TH group's post-arrest temperature was significantly lower than control's (33.6 ± 0.2 °C vs 34.7 ± 0.5 °C, p < 0.001). There was no difference between the groups in safety/efficacy measures, including arrhythmia, infections, chest-tube output, or neuroimaging abnormalities, nor in hospital survival (TH 61.5% vs control 59.1%, p = NS). Significantly more controls had seizures than TH patients (26.1% vs. 4.0%, p = 0.04). Almost all seizures were subclinical and occurred more than 24 h post-arrest. Conclusion: Our data show that pediatric CHD patients who suffer cardiac arrest can be treated effectively and safely with TH, which may decrease the incidence of seizures.